GAMBARAN FAKTOR PENYAKIT IBU YANG BERISIKO TERHADAP KEJADIAN BBLR DI RSUD DR. MARGONO SOEKARJO PURWOKERTO - Ema Wahyuningrum; Etika Kurnia Utami (Viva Medika, 2012)
Background: The incidence of Low Birth Weight (LBW) in Indonesia by 9% -30%, while in theHospital Prof. Dr. Margono Soekarjo LBW incidence in 2011 there 821 (22.44%) of the total3658 deliveries. One cause of low birth weight is a factor of maternal disease such as malaria,sexually transmitted infections, HIV or AIDS, TORCH, anemia, ante partum haemorrhage,hypertension, severe preeclampsia, bladder infection Objectives: To determine the incidence of pregnancy complication factors of maternal with LowBirth Weight Infants (LBW) in hospitals Prof Dr. Margono Soekarjo in 2011. Methods: Thestudy is descriptive method with a retrospective approach, its population was all mothers whodelivered LBW birth in hospitals Prof. Dr. Margono Soekarjo in 2011 as many as 517 maternal,Quata sampling techniques using sampling with a sample of 100 maternity. Secondary type ofdata using the data and instruments used are the master table and analysis data usingpercentage. Results: Most LBW common among women who did not have a maternal diseasefactor ( 50 % ), followed LBW caused by preeclampsia ( 43 % ) , antepartum hemorrhage ( 4 % )and the smallest hypertension ( 1 % ) . Most LBW occurs in many mothers do not have thedisease factors and gestation of prematurity ( 32 % ), and low birth weight occurred in womenwith the disease preeklampsi with gestational age preterm ( 21 % ) . Key words: factor of maternal disease, Infant with Low Birth Weight (LBW)